Effect of two pesticides (Zinc Phosphide and Brodifacoum) on mitotic index and chromosomal changes in bone marrow cells in field and laboratory rats Mus musculus (Journal of the College of Basic Education, 2023)
The genotoxic effect of pesticides (Zinc phosphide and Brodifacoum) which are widely used in rodent control in Iraq was studied on laboratory and field mouse models, Mus musculus, by using cell division index and chromosomal changes in bone marrow cells. The results showed the following:The two pesticides caused a high inhibition in cell division of somatic cells (bone marrow cells), and field mice were more sensitive than laboratory mice to both pesticides. from laboratory rats, Balb\C.